2017
DOI: 10.5539/jsd.v10n4p107
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Awareness and Joint Decision to Adopt Agroforestry and Conservation Agriculture Practices in Zambia

Abstract: Climate change is one of the biggest challenges that small holder farmers face in Sub-Saharan Africa, including Zambia. In response to this, various interventions such as Agroforestry (AF) and Conservation Agriculture (CA) have been promoted within the country so as to enhance uptake among farmers and ultimately mitigate climate change. However, the adoption rates of these technologies has been low. To understand the adoption process several adoption studies have focused on the effects of socio-economic and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…The listed farm households were then stratified into three classes, namely: A, B, and C, based on total area allocated to crops; special crops; numbers of cattle, goats, and chickens raised; and sources of income. To select at least 20 farm households distributed across the three strata in each SEA, systematic sampling was used [41]. While the total sample size for the 2013 survey in this study was 1,231, we used 1,227 observations because of the nonresponse/missing values.…”
Section: Study Area and Data Sourcesmentioning
confidence: 99%
“…The listed farm households were then stratified into three classes, namely: A, B, and C, based on total area allocated to crops; special crops; numbers of cattle, goats, and chickens raised; and sources of income. To select at least 20 farm households distributed across the three strata in each SEA, systematic sampling was used [41]. While the total sample size for the 2013 survey in this study was 1,231, we used 1,227 observations because of the nonresponse/missing values.…”
Section: Study Area and Data Sourcesmentioning
confidence: 99%
“…In the same frame of thought, Aphunu et al (2007) reported that most farmers claimed to be aware of climate change but, the understanding and the level of knowledge on the impact and adaptation were still low. According to Tembo et al (2017), it was reported that majority of the farmers (77.2%) were aware of issues related to climate change and its consequences on agricultural production and the environment. Also, Oduniyi (2014) indicated that climate change awareness among the small-scale maize farmers in Mpumalanga Province of South Africa was low.…”
Section: Literature Reviewmentioning
confidence: 99%